Randomized clinical trial: the use of SpeechEasy® in stuttering treatment. Issue 6 (8th June 2016) - Ritto, Ana Paula; Juste, Fabiola Staróbole; Stuart, Andrew; Kalinowski, Joseph; de Andrade, Claudia Regina Furquim
Abstract: Background: Numerous studies have demonstrated the benefit of devices delivering altered auditory feedback (AAF) as a therapeutic alternative for those who stutter. Aims: The effectiveness of a device delivering AAF (SpeechEasy®) was compared with behavioural techniques in the treatment of stuttering in a randomized clinical trial. Methods & Procedures: Two groups of adults who stutter participated: group 1 consisted of 10 men and one woman aged 21–42 years (mean = 30.0). Group 2 consisted of six men and one woman aged 20–50 years (mean = 35.6). Participants in group 1 were fit with a SpeechEasy® device and were not given any additional training (i.e., supplementary fluency enhancing techniques). Participants used the device daily for 6 months. Participants in group 2 received treatment in the form of a 12‐week fluency promotion protocol with techniques based on both fluency shaping and stuttering modification. Outcomes & Results: There were no statistically significant differences ( p > .05) between groups in participants' stuttered syllables following treatment. That is, both therapeutic protocols achieved approximately 40% reduction in number of stuttered syllables from baseline measures, with no significant relapse after 3 or 6 months post‐treatment. Conclusions & Implications: The results suggest that the SpeechEasy® device can be a viable option for the treatment of stuttering.